Effect of specific mutations of tyrosine-(M)210 on the primary photosynthetic electron-transfer process in Rhodobacter sphaeroides. - Nagarajan, V (1990)
We have measured the rate of the initial electron-transfer process as a function of temperature in reaction centers in a native strain of the photosynthetic bacterium Rhodobacter sphaeroides and two mutants generated by site-directed mutagenesis. In the mutants, a tyrosine residue in the vicinity of the primary electron donor and acceptor molecules was replaced by either phenylalanine or isoleucine. The electron-transfer reaction is slower in the mutants and has a qualitatively different dependence on temperature. In native reaction centers the rate increases as the temperature is reduced, in the phenylalanine mutant it is virtually independent of temperature, and in the isoleucine mutant it decreases with decreasing temperature. At 77 K, the electron-transfer reaction is approximately 30 times slower in the isoleucine mutant than in the native. These observations support the view that tyrosine-(M)210 plays an important role in the electron-transfer mechanism. In the isoleucine mutant at low temperatures, the stimulated emission from the excited reaction center undergoes a time-dependent shift to shorter wavelengths.